Teaching strategies as a predictor of entrepreneurial mindset: implications for innovative teaching strategies - Lope Pihie, Zaidatol Akmaliah; Arivayagan, Keetanjaly (International Journal of Innovative Research in Technology & Science (IJIRTS), 2017)
The aim of this study is to offer innovative teaching strategies in Entrepreneurship Education towards nurturing entrepreneurial mindset among university students. The teaching strategies focused on educator-centered teaching and learner-centered teaching to stress the importance to cultivate innovative teaching strategies as a key way to improve the current practices of EE in universities. This article uses extensive reviews of literature in the fields of education and entrepreneurship to provide a bridge between innovative teaching strategies and current teaching practices in universities to build entrepreneurial mindset among university students. Findings indicated that teaching strategies such as business plan, presentation of business projects, discussion, doing real business and lecture are the most engaging teaching methods been used to stimulate entrepreneurial awareness and improve students’ entrepreneurial mastery skills in producing entrepreneurial mindset among university students. This approach also identify that educator-centered teaching strategies are the predictor to students’ entrepreneurial mastery skills followed by student-centered teaching strategies are the predictor to create entrepreneurial awareness among university students. This article contribute sheds a new light, on the concept of innovative teaching to enhance entrepreneurial awareness and improve students' entrepreneurial mastery skills in producing entrepreneurial mindset among university students.